Heterogeneous Effects of Fibroblast-Myocyte Coupling in Different Regions of the Human Atria Under Conditions of Atrial Fibrillation - Sánchez, Jorge; Gomez, Juan F.; Martinez-Mateu, Laura; Romero, Lucia; Saiz, Javier; Trenor, Beatriz (Frontiers in Physiology, 2019)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and is characterized by an alteration in the action potential (AP) propagation. Under persistent AF myocytes undergo electrophysiological and structural remodeling, which involves fibroblasts proliferation and differentiation, modifying the substrate for AP propagation. The aim of this study is to analyze during AF the effects of fibroblasts coupling to myocytes on AP and its propagation in different regions of the atria. Isolated myocytes were coupled to a different number of fibroblasts, using established AP models, and tissue simulations were performed by randomly distributing fibroblasts. Fibroblast formulations were updated according to recent experimental data. Additionally, five ion current conductances (gto, gKr, gKs, gK1, and gCaL) of the myocyte model were modified to simulate AP heterogeneity in four different regions of the atria, right atrium posterior wall (RA), crista terminalis (CT), left atrium posterior wall (LA), and the pulmonary vein (PV), according to experimental and computational studies. Results from coupled myocyte-fibroblast simulations suggest that a more depolarized membrane potential and a greater membrane capacitance of the fibroblast have a greater impact on action potential duration (APD) and maximum depolarization velocity of the myocyte. The number of coupled fibroblasts and the stimulation frequency were determinant factors altering myocytes AP. Strand simulations showed that conduction velocity (CV) tended to homogenize in all regions. In addition, the regions corresponding to the left atrium were more likely to be affected by fibroblasts and AP propagation block was more likely to occur. The PV region was the most affected, even with low fibroblasts density. Moreover, in 2D simulations wavebreaks were observed in the low density (10%) central fibrotic zone, and when the density of fibroblasts increased (40%) propagation in the fibrotic region was practically blocked. Additionally, with 10% and 20% densities the width of the vulnerable window increased with respect to control, but with 40% the width of the vulnerable window decreased. In conclusion, structural remodeling characteristics heterogeneously affect AP propagation and features in the different zones of the atria. Myocytes from the left atria are more sensitive to fibroblasts coupling and structural remodeling.